A sonographer's guide to the clinical utility of left ventricular speckle tracking strain. Issue 4 (1st September 2020) - Jin Wang, Nikolas; Perry, Rebecca
Abstract: Speckle tracking strain (STS) is an advanced echocardiographic modality that is being increasingly implemented as part of the routine clinical echocardiographic assessment. It can overcome many of the limitations of left ventricular ejection fraction (LVEF), as STS also accounts for segmental LV function and detects multi‐directional components of myocardial deformation. Furthermore, it is able to detect sub‐clinical changes in LV function, which may not be reflected by the LVEF. This may allow more opportunity for intervention prior to the development of overt heart failure in patients with conditions, or undergoing treatments, that increase the risk of LV dysfunction, such as diabetes mellitus, hypertension and some chemotherapy treatments. Moreover, STS may assist in differentiation of aetiology in patients with increased LV wall thickness, as well as assisting with better timing of surgery for patients with valvular disease.